Three years on: Assessing power sector and renewable energy manufacturing policy in China since the announcement of dual carbon goals - Herbert Crowther (The Oxford Institute for Energy Studies, 2023)
China's 'Shuangtan' (dual carbon) pledge is the most consequential climate commitment made by the Chinese government. Announced in September 2020, it commits China to reaching peak CO2 emissions by 2030 and carbon neutrality by 2060. With the nature of the Chinese policy system, however, top-down pledges can be received with varying levels of actual policy implementation. This Paper considers how - three years on - Shuangtan priorities have been reflected in two key areas of Chinese energy/climate policy: the power sector and renewable energy manufacturing. In each of these areas, this Paper details specific post-Shuangtan policy changes. In particular, how these post-Shuangtan policy actions differ from their pre-Shuangtan predecessors, and what they indicate about the future of power sector and renewable energy manufacturing policy. In these changes, it also seeks to evaluate whether Shuangtan represented a 'critical juncture' in specific areas of Chinese energy/climate policy, and offers early thoughts on what the first few years of Shuangtan implementation indicate about Shuangtan's long-term implementation.
Keywords: 330; Coal; decarbonization; Dual carbon; energy security; green industry; net-zero; Power Sector; renewable energy manufacturing; Shuangtan